Degradasi Zat Warna Methyl Orange dengan Katalis TiO2 Menggunakan Metode Fotosonolisis - Suci Ramadhani; Hary Sanjaya; Yohandri Yohandri (Departemen Kimia FMIPA UNP, 2023)
Research on the degradation of methyl orange has been carried out using the photosonolysis method with the help of a TiO₂ catalyst. This study aims to determine how the effect of adding catalyst mass to the degradation of methyl orange and to determine the optimum time to degrade methyl orange. The variation of the mass of the catalyst used to degrade the methyl orange dye is from 0 grams to 0.25 grams, while the time variation is in the range of 30 minutes to 150 minutes with a 30 minute interval. The results of the measurement of the maximum wavelength and the color of methyl orange using a UV-Vis spectrophotometer were 462.8 nm with an absorbance value of 0.772. In the variation of the catalyst mass, the maximum mass obtained at 0.1 grams of TiO₂ catalyst with %D obtained was 23.46% while for the variation of the degradation time the optimum time was obtained at 120 minutes with the %D result of 32.04%. In this study, the presence of hydroxyl radicals produced during the photosynthesis process plays an important role in the process of degrading methyl orange.